Unusual complication of an Alaskan cruise: thinking outside the box. Issue 2 (26th February 2019) - Bhandare, Deepti; Ruchi, Rupam
Abstract : A 69-year-old man with a medical history of hypertension and diabetes presented with altered mental status once he returned from a 14-day Alaskan cruise. An extensive workup for stroke was negative. His physical examination was normal without any focal motor deficits, but he had developed memory loss and paresthesia. He admitted to eating a lot of fish when he was in Alaska. The whole-blood mercury level was found to be elevated. He was managed conservatively and his symptoms resolved completely in a few days. This led to a diagnosis of organic mercury toxicity.